Simple and Task-oriented Mirror Therapy for Upper Extremity Function in Stroke Patients: A Pilot Study - Young-Rim Paik; Su-Kyoung Kim; Jae-Shin Lee; Byoung-Jin Jeon (SAGE Publishing, 2014)
Objective/Background: To compare the effects of simple and task-oriented mirror therapies on upper extremity function in stroke patients with hemiplegia. Methods: A single-subject, reversal (applied behaviour analysis) research design was used, and the study included four patients and two treatments. Treatment 1 involved simple mirror therapy that was performed using simple upper limb movements. Treatment 2 involved task-oriented mirror therapy that required each patient to perform functional movements associated with the tasks of daily living. Changes in upper extremity function were assessed during 23 sessions using box and block test, cube carry, and card turning tests. The Fugl-Meyer Assessment of upper extremity function was also performed. Results: The upper extremity function of all patients increased after mirror therapy. However, the improved upper extremity function of the patients undergoing simple mirror therapy was not maintained after the conclusion of the therapy. By contrast, the improved upper extremity function of the patients receiving task-oriented mirror therapy continued to improve, even after therapy cessation. Conclusion: Task-oriented mirror therapy in stroke patients provided more effective improvement in the upper extremity function of the hemiplegic stroke victims.